ASTD handbook : the definitive reference for training & development - Biech, Elaine; Biech, Elaine; American Society for Training and Development (ASTD Press, 2014)
In today's parlance, smartboard is the new chalkboard, and for the profession of workplace training and development, the new and completely revised 2nd edition of the ASTD Handbook, launching at ASTD's annual International Conference & Exposition in May 2014, will drive thousands to the single best resource for every practitioner and occasional trainer. The ASTD Handbook: The Definitive Reference for Training & Development, 2nd edition, more than a year in the making, maintains the authority and credibility of ASTD's first Handbook (2008), incorporates the new competencies of the profession, and now includes more than 85 percent new and never-before published content that will drive buyers of the 1st edition to the check-out line. Covering vital content on technology and application changes of the last few years, authored by world class training and development authorities, this 2nd edition goes beyond anything ASTD has published to date.
Keywords: Employees : Training of; Commerce; Business & Economics; Marketing & Sales